ANALISIS MENGENAI PERTANGGUNGJAWABAN KOMANDO TERHADAP KEJAHATAN SEKSUAL DAN BERBASIS GENDER (KSBG) YANG DILAKUKAN OLEH BAWAHAN (DITINJAU DARI PUTUSAN ICC NO. ICC-01/05-01/08 DALAM KASUS PROSECUTOR V. JEAN-PIERRE BEMBA GOMBO) - Bella Kurnia Putri (Faculty of Law Universitas Sebelas Maret, 2024)
This study examines the legal argument of the doctrine of command responsibility in relation to sexual and gender based crimes in the light of the case of Prosecutor v. Jean Pierre Bemba Gombo (NO. ICC-01/05-01/08). To achieve such aim, the author analyzed the ICC Trial Chamber and Appeals Chamber judgements of the Gombo’s cases and was using a statutory, case, and conceptual approaches. The author argues that the Trial Chamber judgement to sentence Gombo with 18 years of prison based on command responsibility under article 28 (a) of the Rome Statute is legally in compliance with international criminal law in which Gombo’s actions have fulfilled all the elements of command responsibility.The Trial Chamber’s judgement was also in line with international norms applicable in other areas of international law, such as international humanitarian law and international human rights law which prohibit any form of sexual violence. However, the Appeals Chamber’s judgement to acquit Gombo from all charges was rather controversial as there was a change of standard of review and a different view of the “necessary and reasonable measure” as one of the elements required in crimes relates to command responsibility.